Vaccination for village chickens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
David Daka of the Zambia Institute of Animal Health discusses how small scale farmers can manage Newcastle disease vaccination for their poultry flocks.